Effect of Root Canal Shaping Type on the Amount of Coronal and Apically Extruded Debris (In-Vitro Study) (Journal of Hama University, 2024)
The debris that exceed the apical can cause inflammation of the periapical tissues, which may develop into a flare-up. Therefore, the research aims to evaluate the effect of root canal shaping type on the amount of coronal and apically extruded debris.Materials and methods: The sample consisted of 72 single root canal teeth, the length of which was standardized to 20 mm and randomly distributed into 6 equal groups (n=12) according to the canal shaping type as follows: Group 1 (Crown-Down Technique), Group 3 (Mtwo®, Rotation System), Group 4 (WaveOne® Gold, Reciprocation System), Group 5 (GG+ Mtwo®), Group 6 (GG+ WaveOne® Gold), The apical debris collector was handcrafted; As for the coronary extruded debris, they were collected from the preparation file by using the Cuveets tubes of the spectrophotometer that was used to measure the debris density.   Statistical analyzes were performed using the One Way Anova test for independent samples, the T Test for Paired Samples. (WaveOne® Gold) caused apical and coronal extrusion of debris more than (Mtwo®), and the amount of apical extrusion in the groups from least to most was as follows: Mtwo®, (GG+ Mtwo®), WaveOne® Gold, (GG+ WaveOne® Gold), (Crown-Down Technique), while the amount of coronal extrusion in the groups from least to most was as follows: Mtwo®, (GG+ WaveOne® Gold), (GG+ Mtwo®), (Crown-Down Technique), WaveOne® Gold. All types of canal preparation caused apically and coronary extrusion of the debris. The reciprocational system caused apical and coronal extrusion of debris more than the rotational system. The application of Coronal Preflaring reduced this extrusion, but not significantly.
Keywords: The reciprocational system, the continuous rotational system, Root Canal Shaping, extruded debris, Coronal Preflaring.